2004
DOI: 10.1046/j.1600-6143.2003.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Chronic Kidney Disease in Renal Transplant Recipients

Abstract: The National Kidney Foundation has developed guidelines for the diagnosis and classification of chronic kidney disease (CKD) but it is not known whether these are applicable to renal transplant recipients. This study determined the prevalence of CKD according to the stages defined in the guidelines, the complications related to CKD and whether the prevalence of complications was related to CKD stage in 459 renal transplant recipients. CKD was present in 412 patients (90%) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
95
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 24 publications
12
95
0
1
Order By: Relevance
“…The CKD-related causes for poor VD status were already outlined. The prevalence of CKD stage 3 and over in our department ranges between 49 and 58% over the last 4 years, which is in accordance with or even better than the results of other centers [72,73]. Table 9 summarizes the possible causes of VD insufficiency after KTx with the possible pathophysiological mechanisms involved.…”
Section: Impaired Vitamin D Metabolism After Kidney Transplantation: supporting
confidence: 85%
“…The CKD-related causes for poor VD status were already outlined. The prevalence of CKD stage 3 and over in our department ranges between 49 and 58% over the last 4 years, which is in accordance with or even better than the results of other centers [72,73]. Table 9 summarizes the possible causes of VD insufficiency after KTx with the possible pathophysiological mechanisms involved.…”
Section: Impaired Vitamin D Metabolism After Kidney Transplantation: supporting
confidence: 85%
“…Karthikeyan et al (1) found ferritin levels Ͻ100 ng/ml in 50% of kidney transplant patients whose transplant function corresponded with stages 3 through 5 CKD and transferrin saturation Ͻ20% in 75% of patients with stage 5 CKD. Zheng et al (20) followed 39 consecutive kidney transplant recipients during the first 12 weeks after transplantation, quantified the amount of blood loss, and estimated iron losses.…”
Section: Epo and Iron Deficiencymentioning
confidence: 99%
“…Anemia, a risk factor for cardiovascular events in patients with chronic kidney disease (CKD), may be relevant to kidney transplant recipients because the majority of these recipients have an estimated GFR (eGFR) of Ͻ60 ml/min per 1.73 m 2 (1)(2)(3). In addition, anemia may lead to other adverse outcomes, such as impaired cognition, reduced quality of life, and decreased exercise capacity in patients with CKD and ESRD (4,5).…”
mentioning
confidence: 99%
“…In generally, the glomerular filtration rate (GFR), is considered to be the best index of overall kidney function [13,14] , also an indicator of longterm graft survival [15] , and an independent risk factor for cardiovascular mortality [16,17] , the primary cause of death in kidney transplant recipients [17,18] . Of note, like in non-transplant chronic kidney disease, prevalence of complications related to loss of renal function such as hypertension, anemia and abnormal mineral metabolism increases significantly as the GFR declines [19] . Another important point is that the decline in GFR is also related with increased health care costs, and over the two years, transplantation was both more effective and less costly than dialysis [2,3] .…”
Section: Introductionmentioning
confidence: 99%